Regional integration in Bay of Bengal region in post-COVID-19 period - Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2021)
Bay of Bengal countries have been affected heavily by the ongoing Coronavirus pandemic. This article argues that the regional cooperation could help in reducing the costs of pandemic-driven barriers. The responses to the Corona pandemic also suggest a greater scope of regional cooperation among the countries in the Bay of Bengal region. Regional integration may help the Bay of Bengal countries overcome divisions that impede the flow of trade in goods and services, people and ideas, particularly when all members have been facing a common challenge to beat the Coronavirus pandemic. This paper briefly discusses the major challenges being faced by the Bay of Bengal countries, and the way forward in the post-COVID-19 period. It presents the trends in economic growth in the region, which has been the key to regional economic integration, and analyses the likely economic loss due to the COVID-19 pandemic. The article discusses the magnitude of the Coronavirus pandemic in the Bay of Bengal region, followed by a discussion on the progress and achievements in regional cooperation in the Bay of Bengal region with particular reference to the pandemic period. It also presents the opportunities and the regional response to deal with the ongoing pandemic.
Keywords: F1; F13; 330; Bay of Bengal; BIMSTEC; Trade; Regional integration; COVID-19